Ki-67 Immunohistochemistry Examination in Pityriasis Rubra Pilaris - Diana Kartika Sari; Cita Rosita Sigit Prakoeswa; Troef Soemarno (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2014)
Background: Pityriasis rubra pilaris (PRP) is a papulosquamous disorder of unknown etiology. PRP is often difficult to be distinguished with psoriasis in early phase of the disease. Purpose: To deliver information about Ki-67 immunohistochemistry examination in PRP. Reviews: The diagnosis of PRP can be established by histological examinations or even immunohistochemistry. The best treatment options are retinoids, photochemotherapy (PUVA), and antimetabolites (methotrexate). Conclusion: Immunohistochemistry examination can provide complete feature to distinguish between PRP and psoriasis because of it's high specifity.Key words: Ki-67 immunohistochemistry, pityriasis rubra pilaris, diagnosis.